Potential benefits of a virtual, home-based combined exercise and mindfulness training program for HSC transplant survivors: a single-arm pilot study - David D. F. Ma; Kate Fennessy; David Kliman (BMC, 2022)
Abstract Purpose Impaired quality of life (QOL) including reduced physical fitness is a recognized late effect of hemopoietic cell transplantation (HCT). Guided exercise and mindfulness-based stress management (MBSM) programs have shown promise, mainly in the inpatient setting. We aimed to examine the feasibility of a virtual, home-based, combined exercise and MBSM program. Methods Patients attending post-HCT clinic were invited to participate in this single-arm pre-post study. Eligibility criteria included age 18-75 years, > 6 months post allogeneic HCT. Consented participants attended an in-person session, followed by weekly exercise and MBSM training for 6 weeks via videoconferencing. Assessments were performed pre-training, and at 3-, 6- and 12-months and compared using a linear mixed effects model. Results 21 of 24 patients consenting to the study completed the program (median age 56 years [IQR 46-62], median time post-HCT 37 months [IQR 26-46]). Six-minute walk test scores were significantly higher at 3 (mean difference 79.6, 95%CI 28-131, ES 0.55) and 12 months (mean difference 48.4, 95%CI 13-84, ES 0.33) compared to baseline. Sit-to-stand test was significantly higher at 3 (mean difference 4.4, 95%CI 1.4-7.4, ES 0.68) and 12 months (mean difference 3.9, 95%CI 0.24-7.6, ES 0.61). Dominant hand grip was significantly stronger at 3 (mean difference 0.16, 95%CI 0.04-0.28, ES 0.45), and 12 months (mean difference 0.21, 95%CI 0.08-0.24, ES 0.62). Significantly higher FACT-BMT total (mean difference 6.9, 95%CI 1.5-12.4, ES 0.49) and FACT-G scores (mean difference 5.2, 95%CI 1.4-9.1, ES 0.48) were found at 3 months. Over 80% of participants rated the virtual combined modal program highly and no adverse events were reported. Conclusion A 6-week virtual, home-based exercise and MBSM program was an acceptable, and potentially effective intervention for sustained improvement of some physical capacity and QOL outcomes in HCT survivors. Virtual-based healthcare service is highly relevant particularly during pandemics. To our knowledge, this study has the longest follow-up observation period for Internet based combined modality training program reported to date and warrants additional investigation. Trial Registration Research protocol approved by St Vincent's Hospital Ethics Committee (HREC 12/SVH/175), approved 27/09/2012, trial commenced 24/05/13 and the first participant 07/06/13. Retrospectively registered with ANZCTR (ACTRN12613001054707) 23/09/2013.